ANALISIS PENDISTRIBUSIAN DANA ZAKAT PRODUKTIF DALAM PENGEMBANGAN EKONOMI DAN PENINGKATAN PENDAPATAN MUSTAHIQ - Nurhayati, Siti; Sulaeman, Sulaeman; Suherman, Acep (COMPETITIVE, 2023)
This study aims to identify and explain the distribution of productive zakat funds in developing the mustahiq economy and income, especially those carried out by the National Amil Zakat Agency of Sukabumi Regency. To reveal these problems, researchers conducted research using qualitative methods with a descriptive approach. Where the data obtained through observation, interviews and documentation. Based on the results of the study, it shows that the distribution of productive zakat carried out by BAZNAS Sukabumi Regency is by using the Sukabumi Sejahtera program and realized by the Z-Mart (Zakat Mart) program. The form of assistance provided is in the form of product/goods capital assistance requested in accordance with the application for RAB which was prepared by the previous mustahiq. The mustahiq who received the program assistance admitted that they felt helped and felt an increase in both income and spirituality. Every mustahiq recipient of the program will be given an infaq box. This aims to raise awareness in the recipients of zakat will give infaq, and as evidenced by the collection of infaq from each mustahiq every month. In addition, in the distribution of productive zakat, there is also a mentoring process which aims for the Z-Mart program to run well.